The value of touch imprint cytology and frozen section for intra-operative evaluation of axillary sentinel lymph nodes - Memar, Bahram; Sadeghi, Ramin; Ayati, Narjes-Khatoon; Aledavood, Seyed Amir; Tghizadeh, Ali; Naseri, Shahram; Forghani, Mohammad Naser; Homaee, Fatemeh; Abdollahi, Ali (Polish Journal of Pathology, 2010)
Background : Sentinel lymph node (SLN) biopsy is a procedure of choice to determine the axillary involvement in breast cancer. The most important intraoperative evaluation methods are touch imprint cytology (TIC) and frozen section (FS). Each of these techniques has its own drawbacks and it is still unclear which is preferred. Material and methods : 97 consecutive patients with recently diagnosed breast cancer and no clinical evidence of lymph node involvement were included in the study. The SLN was determined with lymphoscintigraphy. Touch imprint cytology and FS were performed and their results were compared with permanent histopathological examination. Results : Using a permanent section as the gold standard TIC showed sensitivity of 71.4%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 88.7%. These figures were 87.5%, 98.5%, 96.5%, and 95% for FS, respectively. Conclusions : Frozen section is a reliable method for SN assessment during surgery. Using the frozen section during surgery can give the surgeon an opportunity to avoid the second surgery. Touch imprint cytology is also a reliable method for intra-operative SN evaluation. Due to its high predictive value, TIC can be used first in the surgery room and FS can be saved for cases with negative results of TIC.